# Prove $\frac{1}{1 \cdot 3} + \frac{1}{3 \cdot 5} + \frac{1}{5 \cdot 7} + \cdots$ converges to $\frac 1 2$

Show that $$\frac{1}{1 \cdot 3} + \frac{1}{3 \cdot 5} + \frac{1}{5 \cdot 7} + \cdots = \frac{1}{2}.$$

I'm not exactly sure what to do here, it seems awfully similar to Zeno's paradox. If the series continues infinitely then each term is just going to get smaller and smaller.

Is this an example where I should be making a Riemann sum and then taking the limit which would end up being $1/2$?

• The magic words are "telescoping series". Jul 31, 2012 at 23:17
• Thank you for the magic words, I really just needed a push in the right direction! Jul 31, 2012 at 23:19
• @JackThompson, co may be you should write your own an answer to this question? Jul 31, 2012 at 23:20
• The magic words are a push in the right direction. You are supposed to take the hint to look up the magic words and see how to use what you find to solve the problem. Or maybe you did that - it's not clear to me from what you've written. Aug 1, 2012 at 1:55

Solution as per David Mitra's hint in a comment.

Write the given series as a telescoping series and evaluate its sum:

$$\begin{eqnarray*} S &=&\frac{1}{1\cdot 3}+\frac{1}{3\cdot 5}+\frac{1}{5\cdot 7}+\cdots \\ &=&\sum_{n=1}^{\infty }\frac{1}{\left( 2n-1\right) \left( 2n+1\right) } \\ &=&\sum_{n=1}^{\infty }\left( \frac{1}{2\left( 2n-1\right) }-\frac{1}{ 2\left( 2n+1\right) }\right)\quad\text{Partial fractions decomposition} \\ &=&\frac{1}{2}\sum_{n=1}^{\infty }\left( \frac{1}{2n-1}-\frac{1}{2n+1} \right) \qquad \text{Telescoping series} \\ &=&\frac{1}{2}\sum_{n=1}^{\infty }\left( a_{n}-a_{n+1}\right), \qquad a_{n}= \frac{1}{2n-1},a_{n+1}=\frac{1}{2\left( n+1\right) -1}=\frac{1}{2n+1} \\ &=&\frac{1}{2}\left( a_{1}-\lim_{n\rightarrow \infty }a_{n}\right) \qquad\text{see below} \\ &=&\frac{1}{2}\left( \frac{1}{2\cdot 1-1}-\lim_{n\rightarrow \infty }\frac{1 }{2n-1}\right) \\ &=&\frac{1}{2}\left( 1-0\right) \\ &=&\frac{1}{2}. \end{eqnarray*}$$

Added: The sum of the telescoping series $\sum_{n=1}^{\infty }\left( a_{n}-a_{n+1}\right)$ is the limit of the telescoping sum $\sum_{n=1}^{N}\left( a_{n}-a_{n+1}\right)$ as $N$ tends to $\infty$. Since

$$\begin{eqnarray*} \sum_{n=1}^{N}\left( a_{n}-a_{n+1}\right) &=&\left( a_{1}-a_{2}\right) +\left( a_{2}-a_{3}\right) +\ldots +\left( a_{N-1}-a_{N}\right) +\left( a_{N}-a_{N+1}\right) \\ &=&a_{1}-a_{2}+a_{2}-a_{3}+\ldots +a_{N-1}-a_{N}+a_{N}-a_{N+1} \\ &=&a_{1}-a_{N+1}, \end{eqnarray*}$$

we have

$$\begin{eqnarray*} \sum_{n=1}^{\infty }\left( a_{n}-a_{n+1}\right) &=&\lim_{N\rightarrow \infty }\sum_{n=1}^{N}\left( a_{n}-a_{n+1}\right) \\ &=&\lim_{N\rightarrow \infty }\left( a_{1}-a_{N+1}\right) \\ &=&a_{1}-\lim_{N\rightarrow \infty }a_{N+1} \\ &=&a_{1}-\lim_{N\rightarrow \infty }a_{N} \\ &=&a_{1}-\lim_{n\rightarrow \infty }a_{n}.\end{eqnarray*}$$

• Not leaving much for OP to do. Aug 1, 2012 at 1:57
– Did
Aug 1, 2012 at 6:20
• @GerryMyerson I agree. I will take your words into account in future answers. Aug 1, 2012 at 8:16
• @did I agree. I will take your words into account in future answers. Aug 1, 2012 at 8:17

You can prove it with partial sums: $$S_n=\sum_{k=1}^n\frac{1}{(2k-1)(2k+1)}=\sum_{k=1}^n\left(\frac{1}{2(2k-1)}-\frac{1}{2(2k+1)}\right)=\frac{1}{2}\left(\sum_{k=1}^n\frac{1}{2k-1}-\sum_{k=2}^{n+1}\frac{1}{2k-1}\right)$$ $$=\frac{1}{2}\left(\frac{1}{2(1)-1}-\frac{1}{2(n+1)-1}\right)=\frac{1}{2}-\frac{1}{2(2n+1)}$$ Hence, $$\sum_{k=1}^\infty\frac{1}{(2k-1)(2k+1)}=\lim_{n\to\infty}S_n=\lim_{n\to\infty}\left(\frac{1}{2}-\frac{1}{2(2n+1)}\right)=\frac{1}{2}$$

Here is an intuitive way to image this problem.
Imagine a teacher gives you a test with an odd number of problems. You get the first problem incorrect. Then with the next two problems, you miss one and get one right. As the number of problems increases to infinity, your score will approach 1/2( or 50 %)

1 problem test , your score is 0/1
3 problem test , your score is 1/3
The difference bewtween 1/3 and 0/1 is 1/3
5 problem test , your score is 2/5
The difference between 2/5 and 1/3 is 1/15
7 problem test , your score is 3/7
The difference between 3/7 and 2/5 is 1/35

(2n-1) problem test , your score is (n-1)/(2n-1)
(2n+1) problem test, your score is (n)/(2n+1)

The difference of your score between a (2n+1) test and a (2n-1) test is:
(n+1)/(2n+1) - (n)/(2n-1) which simplifies to
1/(2n-1)(2n+1)

The sum of this series (starting with n =1 ) goes to 1/2

PS, you can use this idea to prove that 1/2 + 1/6 +1/12 +1/20 +... goes to 1
In this example, you miss the first problem on the test and then get the rest correct. As the number of problems goes to infinity, your score approaches 1( or 100%)

consider,$$f(n)=\frac{1}{(2n-1) \cdot (2n-1+2)}$$

where $n$ is a natural number

$$\sum_{n=1}^\infty f(n)=\sum_{n=1}^\infty\frac{1}{(2n-1) \cdot (2n+1)}$$

Let, $$\sum_{n=1}^{\infty} f(n) = S$$

i.e. $$S=\sum_{n=1}^\infty\frac{1}{(2n-1)\cdot(2n+1)}$$ i.e. $$S=\sum_{n=1}^\infty(\frac{1}{2})(\frac{1}{2n-1} - \frac{1}{2n+1})$$

i.e. $$S=(\frac{1}{2})\left(\sum_{n=1}^\infty(\frac{1}{2n-1} - \frac{1}{2n+1})\right)$$

i.e. $$S=\lim_{n \to \infty}\left((\frac{1}{2})(\frac{1}{1} - \frac{1}{3}) + (\frac{1}{2})(\frac{1}{3} - \frac{1}{5}) + (\frac{1}{2})(\frac{1}{5} - \frac{1}{7}) + \cdots + (\frac{1}{2})(\frac{1}{2n-1} - \frac{1}{2n+1})\right)$$

i.e. $$S=\lim_{n \to \infty}(\frac{1}{2})\left((\frac{1}{1} - \frac{1}{3}) + (\frac{1}{3} - \frac{1}{5}) + (\frac{1}{5} - \frac{1}{7}) + \cdots + (\frac{1}{2n-1} - \frac{1}{2n+1})\right)$$

i.e. $$S=\lim_{n \to \infty}(\frac{1}{2})\left(\frac{1}{1} - \frac{1}{2n+1}\right)$$

i.e. $$S=(\frac{1}{2})\left(\frac{1}{1} - \lim_{n \to \infty}(\frac{1}{2n+1})\right)$$

i.e. $$S=(\frac{1}{2})\left(\frac{1}{1} - 0\right)$$

i.e. $$S=(\frac{1}{2})\left(\frac{1}{1}\right)$$

i.e. $$S=\frac{1}{2}$$

• I think you want $f(n)=\frac 1{(2n-1)(2n+1)}$ to make $S$ the sum of it. Then the first line starting with i.e. is incorrect, as it would include $\frac 1{2\cdot 4}$ and others with even numbers in the denominators. This gets cancelled in the third line starting with i.e. Aug 1, 2012 at 3:32
• Aside from the mistakes, what does this add to the earlier answer from Americo? Aug 1, 2012 at 7:23
• Notation: You mean $$\sum_{n=1,3,\dots}^\infty f(n)$$ instead of $$\sum_{n=1,3}^\infty f(n)$$ Aug 2, 2012 at 15:16
• you are right. odd and even numbers both tend to infinity. here odd numbers are considered. Aug 3, 2012 at 3:40
• the latest edition is as per convention Aug 4, 2012 at 17:01